2017
DOI: 10.3390/fermentation3030039
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Membrane Bioreactor Effluent Reuse: A Review of Microbial Safety Concerns

Abstract: Broad and increasing interest in sustainable wastewater treatment has led a paradigm shift towards more efficient means of treatment system operation. A key aspect of improving overall sustainability is the potential for direct wastewater effluent reuse. Anaerobic membrane bioreactors (AnMBRs) have been identified as an attractive option for producing high quality and nutrient-rich effluents during the treatment of municipal wastewaters. The introduction of direct effluent reuse does, however, raise several sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 141 publications
(164 reference statements)
0
13
0
Order By: Relevance
“…For example, up to 10 4 gene copies (GC) of beta-lactamase bla TEM gene, 10 2 GC of beta-lactamase bla CTX-M gene, and 10 2 GC of mecA gene were found to be present in phages isolated from sewage [39]. Recent review papers have collated abundance of ARGs determined by qPCR in various wastewater effluent streams [40,41], while others discussed the use of metagenomics to track and perhaps to assign risks that are associated with ARGs [42][43][44]. An extensive elaboration of the various studies has demonstrated the use of these tools, and therefore will not be reiterated in this paper.…”
Section: Monitoring and Surveillance Of Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, up to 10 4 gene copies (GC) of beta-lactamase bla TEM gene, 10 2 GC of beta-lactamase bla CTX-M gene, and 10 2 GC of mecA gene were found to be present in phages isolated from sewage [39]. Recent review papers have collated abundance of ARGs determined by qPCR in various wastewater effluent streams [40,41], while others discussed the use of metagenomics to track and perhaps to assign risks that are associated with ARGs [42][43][44]. An extensive elaboration of the various studies has demonstrated the use of these tools, and therefore will not be reiterated in this paper.…”
Section: Monitoring and Surveillance Of Antibiotic Resistancementioning
confidence: 99%
“…MF, UF, and NF membranes are commonly applied in tandem with activated sludge treatment as an alternative to a settling tank. LRV of bacterial contaminants reported by MBRs are collated in a recent review paper [41]. When comparing the reported influent and effluent abundances of bacteria, it is apparent that membranes are a well-established barrier to remove bacteria at high LRV, but whether these reported LRVs can be translated to ARB would remain unknown.…”
Section: Treatment Technologies To Remove Arb and Argsmentioning
confidence: 99%
“…However, towards attaining higher efficiency, research focus was moved towards coupling anaerobic bioreactors with membrane filtration units. These systems were seen to offer a more unique and prudent technique over conventional anaerobic method [7]. It simply combines the anaerobic process and membrane technology operating simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies proposed pathways towards enhanced nutrient bioavailability [10,[58][59][60] and improved human health/well-being [61][62][63][64] (including microbiome therapies [63][64][65][66]), advances of interest to contrast the adverse effects of some negative externalities. Furthermore, the design of several works looking at reducing resource dissipation, saving energy [52,69], valorising foods by-products [52,70,71], foods wastes [72][73][74], and wastewater [75][76][77]. Finally, some strategies can preserve microbial diversity associated with food fermentation [78][79][80].…”
Section: Tailored Food Fermentative Processes To Reduce Negative Exte...mentioning
confidence: 99%